Preferences of the Red Flour Beetle, Tribolium castaneum, for Nutritionally Different Dog Foods - Wagner, Kasey; Aikins, M. Jamie; Phillips, Thomas (My University, 2018)
Triboliumcastaneum, known as the red flour beetle (RFB)is a common pest of stored grain and milled grain products.Thisresearch studied how RFBs orient to and lay eggs in their standard flour diet and in two kinds of dog food.We tested whether RFBs have a preference toward two different dog foods, one with low protein, the “Light” food, and the other with high protein, the “Dark” food. We predicted the beetles would prefer the Light kibble with the lower protein.When given the choice between the two foods, 60% of beetlespreferredthe Light product, which had only 20% of the protein as the dark food, which was chosen by 40% of beetles. When the beetles were given the choice between either Light or Dark kibble, vs. their regular flour-based lab diet, flour was the preferred food. However, the two-choice test showed a higher proportion of beetles were in the Light compared to Dark food. These results are important because they will help the pet food industry further understand what the RFBs prefer, and thus help us take appropriate measures to prevent infestation.
Keywords: Fall 2018